2010
DOI: 10.1590/s0124-00642010000200011
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic among periodontal disease, stress, and adverse pregnancy outcomes

Abstract: Objective The aim of this study was to determine the dynamic between periodontitis and stress and the incidence of preterm birth (PTB), low birth weight (LBW) and preterm low birth weight (PLBW) in pregnant women from Pasto, Nariño, Colombia. Methods Forty-six women who attended to "Hospital Local Civil" localized in the city were involved. Periodontal clinical evaluation, pregnancy outcome variables and a stress scale were collected. Data were analyzed using descriptive and analytic statistics. Results The in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Within the last two decades, a large number of cross-sectional, case-control, and cohort observational studies were carried out to investigate periodontal disease as a risk factor for adverse pregnancy outcomes (Arteaga-Guerra et al, 2010), which involved miscarriage, preeclampsia, preterm birth (PTB), low birth weight (LBW), and/or preterm low birth weight (PLBW) (Cruz et al, 2009). Results of these studies presented conflicting findings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the last two decades, a large number of cross-sectional, case-control, and cohort observational studies were carried out to investigate periodontal disease as a risk factor for adverse pregnancy outcomes (Arteaga-Guerra et al, 2010), which involved miscarriage, preeclampsia, preterm birth (PTB), low birth weight (LBW), and/or preterm low birth weight (PLBW) (Cruz et al, 2009). Results of these studies presented conflicting findings.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the majority of studies used community periodontal index (CPI) to describe periodontal status. CPI, as one of the methods for evaluating the prevalence of periodontal disease, had been shown that it could underestimate the true values (Arteaga-Guerra et al, 2010). Therefore, examining six sites of each tooth in a full-mouth scale is necessary, which would make clear understanding of the prevalence of periodontal disease in a particular population.…”
Section: Introductionmentioning
confidence: 99%
“…Twelve studies were cross-sectional [16,17,[28][29][30][31][32][33][34][35][36][37], three were casecontrol [38][39][40] studies, one was a cohort study [41] and two were prospective clinical trial [4,42] studies, comprising 5051 individuals. Two of the studies were conducted only with women [16,34], and two studies did not mention the gender distribution [29,31].…”
Section: Description Of the Studiesmentioning
confidence: 99%
“…Two of the studies were conducted only with women [16,34], and two studies did not mention the gender distribution [29,31]. In most of the studies [4,17,[28][29][30]37,38,[40][41][42], the participants were patients at a university periodontal clinic or private dental practice.…”
Section: Description Of the Studiesmentioning
confidence: 99%
See 1 more Smart Citation